2010
DOI: 10.1021/jm901692q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Alpha-7 Nicotinic Acetylcholine Receptor Agonists Containing a Urea Moiety: Identification and Characterization of the Potent, Selective, and Orally Efficacious Agonist 1-[6-(4-Fluorophenyl)pyridin-3-yl]-3-(4-piperidin-1-ylbutyl) Urea (SEN34625/WYE-103914)

Abstract: Alpha-7 nicotinic acetylcholine receptor (alpha7 nAChR) agonists are promising therapeutic candidates for the treatment of cognitive impairment. We report a series of novel, potent small molecule agonists (4-18) of the alpha7 nAChR deriving from our continuing efforts in the areas of Alzheimer's disease and schizophrenia. One of the compounds of the series containing a urea moiety (16) was further shown to be a selective agonist of the alpha7 nAChR with excellent in vitro and in vivo profiles, brain penetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Complemented by experiments using site-directed mutagenesis and/or sulfhydryl reagents to modify accessibility to the cysteines in the LBD, data further highlighted the role of key amino acid residues that are thought to contribute to the pharmacophore (Papke et al, 2011a). Computer modeling and docking of molecules based on known structures rapidly expanded the number of molecules that demonstrated selectivity for a7 nAChRs, as illustrated in the medicinal chemistry literature Ghiron et al, 2010;Schrimpf et al, 2012;Kombo et al, 2012;Zanaletti et al, 2012). Computer modeling further pointed to the role of fractional hydrophobicity/ hydrophilicity of the LBD and the contribution of the cation-p interaction of the ligand's basic nitrogen atom with tryptophan 149 of the LBD (Kombo and Bencherif, 2013).…”
Section: B Functional Properties Of A7 Nicotinic Acetylcholine Recepmentioning
confidence: 99%
“…Complemented by experiments using site-directed mutagenesis and/or sulfhydryl reagents to modify accessibility to the cysteines in the LBD, data further highlighted the role of key amino acid residues that are thought to contribute to the pharmacophore (Papke et al, 2011a). Computer modeling and docking of molecules based on known structures rapidly expanded the number of molecules that demonstrated selectivity for a7 nAChRs, as illustrated in the medicinal chemistry literature Ghiron et al, 2010;Schrimpf et al, 2012;Kombo et al, 2012;Zanaletti et al, 2012). Computer modeling further pointed to the role of fractional hydrophobicity/ hydrophilicity of the LBD and the contribution of the cation-p interaction of the ligand's basic nitrogen atom with tryptophan 149 of the LBD (Kombo and Bencherif, 2013).…”
Section: B Functional Properties Of A7 Nicotinic Acetylcholine Recepmentioning
confidence: 99%
“…(Ghiron et al 2010). Treatment with WYE-103914 resulted in significantly greater time spent exploring the novel compared to the familiar object demonstrating enhanced retention of the previous learning experience (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…WYE-103914, a selective and potent α7 nAChR agonist (Ghiron et al 2010), was found to be active in multiple memory models in the rat and mouse. These models include the pharmacological disruption of memory using the NMDA antagonist MK-801 in the novel object recognition paradigm in rats, and the delay-induced deficit NOR model in rats, as shown in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations